ABOUT THE METHODS OF CALCULATING THE VOLUME OF A CONIC MULTIFACET IN COMPUTER PROGRAMS - Kutbayev, A.B. (SCIENCE and SOCIETY, 2026)
In this work, methods for computing volumes of cone manifolds for knots in hyperbolic geometry are presented, along with differences between computations performed in the computer programs SnapPy and Wolfram Mathematica 13.2.
Keywords: hyperbolic geometry; cone-manifold; orbifold; hyperbolic volume; invariant